2011
DOI: 10.1021/es201964x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Levels of Serum Perfluorinated Chemicals and Adiponectin in a Young Hypertension Cohort in Taiwan

Abstract: In animals, perfluorinated chemicals (PFCs), specifically perfluorooctanoic acid (PFOA) and perfluorooctane sulfate (PFOS), function as peroxisome proliferator-activated receptor (PPAR) alpha agonists. However, the relevance of animal (primarily rodent) data to humans is unresolved. While plasma adiponectin level is very responsive to PPAR gamma agonist drugs, it has not been determined whether adiponectin level is related to serum PFCs concentrations. In the present study, 287 subjects (12-30 years of age) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 40 publications
(76 reference statements)
1
33
0
Order By: Relevance
“…The measurements of PFAS have been validated (Lin et al, 2013b) and have been demonstrated to have different health effects in this cohort (Lin et al, 2011(Lin et al, , 2013aSu et al, 2014). This study also had several limitations.…”
Section: Discussionmentioning
confidence: 97%
“…The measurements of PFAS have been validated (Lin et al, 2013b) and have been demonstrated to have different health effects in this cohort (Lin et al, 2011(Lin et al, , 2013aSu et al, 2014). This study also had several limitations.…”
Section: Discussionmentioning
confidence: 97%
“…Most animal studies showed that administration of PFAS led to lower levels of circulating lipids (i.e., total cholesterol and triglycerides), but known betweenspecies differences in PFAS toxicokinetics limit the generalizability of animal study findings to humans [1]. Evidence from human studies regarding PFAS exposure and lipids is mixed [11,27,28]. Positive associations between PFASs and total cholesterol, LDL cholesterol, or triglycerides were observed in some cross-sectional and prospective studies [4,8,9,[29][30][31], whereas other studies reported null associations or even inverse associations [11,28,32].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, PFASs can structurally bind to various isoforms of peroxisome proliferatoractivated receptor (PPAR α and PPAR γ ) and the binding affinity of these isoforms is differential with PPAR α being most responsive to PFASs (Vanden Heuvel et al, 2006). The activation of PPAR α and PPAR γ has been linked to the regulation of fatty acid metabolism, inflammation, and glucose homeostasis (Lin et al, 2011;Staels and Fruchart, 2005). Our findings, if true, suggested that the favorable effect of PFOA, PFNA, and PFUA on glucose homeostasis may be due to PPAR α and PPAR γ activation.…”
Section: Discussionmentioning
confidence: 99%